2021
DOI: 10.1371/journal.pone.0249057
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin’s relationship with malnutrition and oxidative stress in adolescents. A pilot study

Abstract: Osteopontin (OPN) is a protein involved in inflammatory illnesses such as fibrosis and cancer; its overexpression in cardiovascular diseases promotes the biomineralization of blood vessels and other soft tissues. Moreover, there is an active component of oxidative stress related with those diseases. The present study relates serum OPN levels with nutritional condition and oxidative stress in a group of adolescents. Anthropometric measurements were performed, and fasting blood samples were analyzed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The influence of weight loss was assessed on OPN status in children and adolescents, who were on a diet and exercise program [ 175 ]. The results revealed a positive relationship between decreased endogenous OPN and diminished body mass index, which confirms the data of a study documenting OPN elevation in overweight and obese subjects [ 176 ]. Interestingly, higher OPN levels were detected in the adipose tissue of morbidly obese patients in association with macrophage infiltration [ 177 , 178 ].…”
Section: General Osteopontin Propertiessupporting
confidence: 88%
“…The influence of weight loss was assessed on OPN status in children and adolescents, who were on a diet and exercise program [ 175 ]. The results revealed a positive relationship between decreased endogenous OPN and diminished body mass index, which confirms the data of a study documenting OPN elevation in overweight and obese subjects [ 176 ]. Interestingly, higher OPN levels were detected in the adipose tissue of morbidly obese patients in association with macrophage infiltration [ 177 , 178 ].…”
Section: General Osteopontin Propertiessupporting
confidence: 88%
“…Also, when MDA is concerned discrepant results were reported between studies. Higher serum MDA levels were shown in some studies [26] [27] [28] [29] [30] , whereas no difference between study groups was found in the others [31] [32] [33] [34] [35] [36] .…”
Section: Discussionmentioning
confidence: 83%
“…The small sample size is one of the limitations of this study. However, previous studies also included a relatively small number of participants [26] [35] [36] . Aztatzi-Aguilar et al [36] included an even smaller number of participants, i.e., 35 students with a median age of 16 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine biomarkers, such as neutrophil gelatinase-associated lipocalin (NGAL), beta-2 microglobulin (β2-M), kidney injury molecule-1 (KIM-1), liver-type fatty acid-binding protein (L-FABP), osteopontin (OPN), and N -acetyl-β-D-glucosaminidase (NAG), have been extensively studied to detect DN among the pediatric population [ 10 ]. Several studies have shown that levels of certain biomarkers were significantly elevated, particularly in obese as compared to normoweight children [ 11 , 12 , 13 , 14 ]. Thus, it is likely that there is close crosstalk between renal injury markers and the pathophysiology of obesity.…”
Section: Introductionmentioning
confidence: 99%